Interplay between two quorum sensing‐regulated pathways, violacein biosynthesis and VacJ/Yrb, dictates outer membrane vesicle biogenesis in Chromobacterium violaceum. (5th May 2020) - Batista, Juliana H.; Leal, Fernanda C.; Fukuda, Taise T. H.; Alcoforado Diniz, Juliana; Almeida, Fausto; Pupo, Mônica T.; da Silva Neto, José F.
Summary: Outer membrane vesicles (OMVs) are lipid nanoparticles released by Gram‐negative bacteria, which play multiple roles in bacterial physiology and adaptation to diverse environments. In this work, we demonstrate that OMVs released by the environmental pathogen Chromobacterium violaceum deliver the antimicrobial compound violacein to competitor bacteria, mediating its toxicity in vivo at a long distance. OMVs purified by ultracentrifugation from the wild‐type strain, but not from a violacein‐abrogated mutant Δ vioABCDE, contained violacein and inhibited several Gram‐positive bacteria. Competition tests using co‐culture and transwell assays indicated that the C. violaceum wild‐type strain killed Staphylococcus aureus better than the Δ vioABCDE mutant strain. We found that C. violaceum achieves growth phase‐dependent OMV release by the concerted expression of two quorum sensing (QS)‐regulated pathways, namely violacein biosynthesis and VacJ/Yrb system. Although both pathways were activated at high cell density in a QS‐dependent manner, the effect on vesiculation was the opposite. While the Δ vioABCDE mutant produced twofold fewer vesicles than the wild‐type strain, indicating that violacein induces OMV biogenesis for its own delivery, the Δ vacJ and Δ yrbE mutants were hypervesiculating strains. Our findings uncovered QS‐regulated pathways involved in OMV biogenesis used by C. violaceum to package violacein into OMVs for interbacterial competition.